Influence of value predispositions, interpersonal contact, and mediated exposure on public attitudes toward homosexuals in Singapore - Detenber, Benjamin H. (2014)
This national survey tracks changes in Singaporeans‘ attitudes toward lesbians and gay men (ATLG) and examines value predispositions, interpersonal contact, and mediated exposure as predictors of ATLG and acceptance of homosexuals. The study replicates and extends research done previously and addresses temporal shifts in values and views. Findings indicate that the relatively small positive change in ATLG from 2005 to 2010 was mainly due to values and demographic factors. The addition of several new predictive variables increased the variance explained for why people hold certain ATLG and their acceptance. Conformity to norms, intrinsic religiosity, Western orientation, interpersonal contact, and mediated exposure were significantly associated with both ATLG and acceptance of homosexuals. Perception of homosexuality as a choice was significantly associated with ATLG but not with acceptance of homosexuals. Asian orientation and extrinsic religiosity showed no significant association with either dependent variable. The findings are discussed in the context of a multi-cultural Asian society and future directions for research.